2008
DOI: 10.1103/physreva.77.013820
|View full text |Cite
|
Sign up to set email alerts
|

Bright-dark solitons and their collisions in mixedN-coupled nonlinear Schrödinger equations

Abstract: Mixed type (bright-dark) soliton solutions of the integrable N-coupled nonlinear Schrödinger (CNLS) equations with mixed signs of focusing and defocusing type nonlinearity coefficients are obtained by using Hirota's bilinearization method. Generally, for the mixed N-CNLS equations the bright and dark solitons can be split up in (N − 1) ways. By analysing the collision dynamics of these coupled bright and dark solitons systematically we point out that for N > 2, if the bright solitons appear in at least two com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(116 citation statements)
references
References 38 publications
3
110
2
1
Order By: Relevance
“…This system (1) admits three types of soliton solutions namely bright-bright, bright-dark, and dark-dark. It was found that the bright solitons exhibit a special type of energy sharing collisions where as the dark solitons always undergo elastic collision [16,18]. The Gram determinant form of the bright N -soliton solution (for arbitrary N ) has been obtained by Kanna et al, [16].…”
Section: Asymptotic Analysis Of Two-soliton Solution Of Manakov Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…This system (1) admits three types of soliton solutions namely bright-bright, bright-dark, and dark-dark. It was found that the bright solitons exhibit a special type of energy sharing collisions where as the dark solitons always undergo elastic collision [16,18]. The Gram determinant form of the bright N -soliton solution (for arbitrary N ) has been obtained by Kanna et al, [16].…”
Section: Asymptotic Analysis Of Two-soliton Solution Of Manakov Systemmentioning
confidence: 99%
“…The above system admits bright soliton solutions for the Manakov (focusing) case and it supports both bright and bright-dark soliton solutions for the mixed-ICNLS case [11][12][13][14][15][16][17][18]. Particularly, the bright multi-soliton solutions of the multicomponent generalization of Manakov system have been obtained by Kanna et al using the Hirota bilinearization method and a detailed investigation on the soliton collisions, such as energy sharing collision and elastic type interactions, have been explored [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, these states have also undergone intense theoretical investigation; see e.g. [45][46][47][48][49][50][51][52][53][54][55] for a number of relevant studies. The prototypical onedimensional model where such states can be found to arise is the coupled GPE [28] of the form:…”
Section: Dark-bright Solitonsmentioning
confidence: 99%
“…Another same analysis, if the variation of Γ j (t) exist, the amplitudes of three soliton pairs will change followingly. Here, in the same way, one can also discuss the dynamic behaviour of other forms of soltion pairs such as two dark-dark soltions [7,46] and two brightdark soltions [47] by the transformation in Section 2.…”
Section: Bright Soliton Pairsmentioning
confidence: 99%